A Case Reporting the Neuro-Rehabilitation of a Patient with Bilateral Multi-Level Lower Extremity Arterial Thrombosis Post COVID -19 - Chawla, Nistara (International Journal of Innovative Research in Medical Science, 2023)
Background: The novel coronavirus (COVID-19 or SARS CoV2) appears to be associated with the risk of thrombosis which is a common consequence of a variety of medical and surgical disorders. These sequelae suggest the presence of coagulopathy induced by COVID-19 infection. Case Report: We present the case of a 63-year-old woman who developed lower limb weakness after undergoing revascularization surgery for multi-level femoral artery thrombosis as a result of SARS-CoV2. After recovery from COVID-19 infection, the patient developed bilateral lower-extremity pain and paralysis. Doppler ultrasound revealed bilateral superficial femoral artery thrombosis, which was later confirmed by angiography. The patient further developed critical limb ischemia and underwent revascularization surgery. Post surgery, patient was unable to ambulate due to marked weakness and sensory deficits in lower extremities. An evidence-based physiotherapy exercise regime was planned for this patient and was followed up for a period of three months. The functional recovery of the patient was documented using two-minute walk test (2 MWT), berg balance scale (BBS) and manual muscle testing of hip, knee and ankle. Results and conclusion: Early tailor-made neuro-rehabilitation plays a significant role in improving the functional status of patients with bilateral lower limb arterial thrombosis post COVID-19.